Thinking Beyond ‘Free Speech’ in Responding to Online Harassment - Croeser, Sky (2016)
Online harassment is a significant problem, and an important movement has emerged in response. However, this activism usually refers back to free speech discourse. I argue that an intersectional approach requires us to explore a more radical rethinking of the political traditions we draw on when responding to online harassment.